Analisis Prediksi Kesulitan Keuangan dengan Metode Altman Z-score, Springate, Zmijewski, dan Zavgren - Nia Arnela Anggraeni; Retna Safriliana (University of Merdeka Malang, 2019)
This study aims to analyze the prediction of financial distress using the Altman model, the Springate model, the Zmijewski model and the Zavgren model in property and real estate companies listed on the Indonesia Stock Exchange. This study uses secondary data, namely the 2016-2017 financial statements using documentation method techniques and analyzed using the Altman model, Springate models, Zmijewski models and Zavgren models. The results of this study indicate that the Altman model of companies experiencing financial distress in 2016 amounted to 5% and in 2017 amounted to 7%. In the Springate model companies that experience financial distress in 2016 amounted to 63% and in 2017 amounted to 60%. In the Zmijewski model companies that experienced financial distress in 2016 and 2017 were 0%. The prediction results for the Zavgren model of the company that experienced financial distress in 2016 amounted to 30% and in 2017 amounted to 42%. The most effective method for prediction of finansial distres sis the Zmijewski method, becouse the model had been high degree of accuracy in predicting the level of finacial distress of the company.